Tribute to Adelina Valdez Colfax Cty pioneer (Springer Tribune, 1967)
Article on a little history on Adelina Valdez a Colfax County Pioneer.
Mater List Item # 5
File location is in the New Mexico File Cabinets
Keywords: Abreu, Adelina; Abreu, J.G.; Beaubien, Petra; Valdez, Emilio; Valdez, Antonio Jose; Quintana, Tonita; Martin, W.P.; Martin, W.P. (Mrs.); Carson, Kit; Abreu, J.G.; Beaubien, Carlos; Maxwell, L.B.; Lee, Stephen; Bent, Charles; Beaubien, Narciso; Abreu Ranch; Valdez Ranch; Vallejo Ranch; Miami Ranch; Maxwell Land Grant; Local History; Biography; Ranchers; Pioneers; Land Owners; Indians; Rayado, New Mexico; Trinidad, Colorado; Miami, New Mexico; Taos, New Mexico; Rio Arriba County, New Mexico